THE BOOK OF CRYPTO the Complete Cuide to Understanding Bitcoin Cryptocurrencies and Digital Assets - HENRI ARSLANIAN (palgrave macmillan, 2019)
This book provides a comprehensive overview of Bitcoin, cryptocurrencies, and digital assets, and their impact on the future of money and finance. It offers a comprehensive, practical, concise, and engaging overview of all the topics that those interested in digital assets need to know, including how Bitcoin and Ethereum work, an overview of the most important digital assets on the market, and a deep dive into the various types ofDigital assets, including cryptocurrencies, stablecoins, central bank digital currencies, utility tokens, security tokens, non-fungible tokens (NFTs), and many more. The book also covers all the basics, including decentralized finance (DeFi), cryptocurrency mining,Cryptocurrency regulations, cryptocurrency investors, cryptocurrency exchanges, and other ecosystem players, as well as the latest global cryptocurrency trends, from Web 3.0 and the Metaverse to decentralized autonomous organizations (DAOs) and quantum computing. This book is authored by a leading industry expert and thought leader who advises some organizations The world's leading provider of digital assets, it is ideal for anyone looking to gain a solid foundation of knowledge in this rapidly growing field and understand its potential impact on the future of money.